Alhagi pseudalhagi Extract Exerts Protective Effects Against Intestinal Inflammation in Ulcerative Colitis by Affecting TLR4-Dependent NF-κB Signaling Pathways - Xu, Xiaoqin; Zhang, Juan; Chen, Liang; Sun, Yu; Qing, Degang; Xin, Xuelei; Yan, Chunyan (Frontiers in Pharmacology, 2021)
Abstract Alhagi pseudalhagi Desv Extract(APE)is the major active fraction extracted from the overground part of Alhagi pseudalhagi Desv.In view of its applied in Uyghur medicine,it could be beneficial for the treatment of ulcerative colitis(UC).The aim of the present study was to investigate the possible beneficial effects of APE on UC mice and to detect the possible mechanisms of underlying these effects. Methods: Acute ulcerative colitis model was established in mice by using dextran sulfate sodium(DSS).Sixty mice were randomly divided into 6 groups:Normal group(NG),UC model group(UG),sulfasalazine group(SG,SASP200mg/kg),low-dose APE group(APE-L,2.82g/kg•d),middle-dose APE group(APE-M,1.41g/kg•d),high-dose APE group(APE-H,0.70g/kg•d).Medicine was given by gavage for 10 days after induction of colitis.Fristly,The serum and colon tissue samples were collected during the experiment,we tested survival signs,body weight changes,disease activity index (DAI),colon length and wet weight of mice after treatment.UC damage include inflammation and ulcer injury of colon mucosa were observed by naked eye observation,hematoxylin and eosin staining (H&E) and scan electron microscopy.The score was performed according to Wallace and Keean's criteria.We measured the expression of tumor necrosis factor α (TNF-α),interleukin (IL)-1β, IL-6 and IL-10 in serum and colon tissues by immunohistochemical assay (ELISA).Additionally,The relative protein of inflammatory as toll-like receptor 4 (TLR4),nuclear factor-kappa B p65 (NF-κB p65),phosphorylation of NF-κB p65 at Ser536 (p-p65 Ser536),Inhibitor kappa B-Kinase β(IK-Kβ), and phosphorylation of p-IK-Kβ (Ser176/180) in colonic mucosal epithelial tissues were detected by Western Blot.The main functional components were preliminarily analyzed and confirmed by UPLC-MS/MS. Results:The UC model was successfully established by using DSS.The results showed that APE treatment repaired the UC injury, and it could reduct the weight loss,attenuate DAI,CMDI,and histological inflammation,significantly downregulated the levels of inflammatory markers include TNF-α, IL-1β and IL-6 of serum and colon tissues on UC model.Meanwhile,APE treatment reduced the key protein of TLR4,and reduced phosphorylation status of p-NF-κB and p-IK-Kβ.The main components of the APE consist of Dihydroquercetin, kaempferol 7-O-glucoside, hyperoside,rutin,kaempferol,isorhamnetin,7,8-dihydroxy flavonoids, kaempferol. Conclusions:To the best of our knowledge,the present study is first to demonstrate that APE exerts protective effect against intestinal inflammation of UC by affecting TLR4-Dependent NF-κB signaling pathways.